Pengaruh Unsur Fe dan Penambahan Grain Refiner Al-5TiB Terhadap Morfologi Fasa Intermetalik dan Sifat Mekanis Pada Paduan Zamak 3 - Surya Irawan; Khairuddin Tampubolon (JOURNAL OF MECHANICAL ENGINEERING MANUFACTURES MATERIALS AND ENERGY, 2021)
In general, in the hot chamber diecasting industry the use of scrap gating and machining has never been optimally used for recycling so that it can become raw material. This is due to the presence of iron impurities (Fe) forming an intermetallic phase which is dissolved into the Zn-Al alloy which can be seen in its microstructure. So that problems arise that will result in defects in the castings and reduce the mechanical properties of the castings. This study aims to determine the effect of adding Al-5TiB modifier as a grain refiner in changing the morphology of the intermetallic phase of the alloy. This research was conducted at the Department of Metallurgy and Materials, FTUI, Depok and the objects were Zinc-Aluminum Zamak 3 and several other supporting metals. This study uses an experimental method. The results of the investigation show that the effect of impurities through the addition of iron (Fe) 0.04% and 0.19% can lead to an increase in the intermetallic phase fraction at the grain boundaries which causes a decrease in tensile strength, impact, and fluidity in Zinc - Aluminum alloys. The addition of 0.5% and 1% Al-5TiB grain refiner to the Zamak 3 master alloy with 0.19% iron (Fe) content resulted in an increase in the mechanical properties and fluidity values of the alloy. This is due to the formation of an intermetallic phase which is more uniformly distributed over the finer grain boundaries.